Demographic factors and awareness of the salaried individual taxpayers on the self-assessment system of taxation: a study in manufacturing companies at Kota Bharu, Kelantan / Tuan Zainun Tuan Mat, Dr. Noraini Mohamad and Siti Haliza Asat - Tuan Mat, Tuan Zainun; Mohamad, Noraini; Asat, Siti Haliza (2005)
This study discusses aspects of tax self-assessment system among salaried individual taxpayers in manufacturing sectors. The objective is to ascertain the demographic characteristics of salaried individual taxpayers, and to establish their level of awareness on the tax self-assessment system, which were to be introduced in year of assessment 2004. The study also explores on the issue of whether there is a potential association between the levels of awareness in relation to the demographic characteristics of the chosen respondents. The survey was conducted through distribution of questionnaires to salaried taxpayers to various numbers of manufacturing companies in Kota Bharu, Kelantan. The findings of the study indicate that quite a number of respondents are still not aware of the existence of the tax self-assessment system that will take place for salaried individual in the year of assessment 2004. As mentioned by the respondents, the lack of information and limited exposure on the system by the Inland Revenue Board (IRB) was part of the problem. The 'wait until last minute' attitude of the taxpayers too is another reason for ignorance in this issue. Therefore, we suggest that the IRB be more proactive in acknowledging the public on the importance of self-assessment system, while the taxpayers on the other hand, should be more attentive to important issues such as the tax-assessment system that will have impact on their financial and social obligations to the government. Both parties should play an active role to ensure the success of the new system.